2015
DOI: 10.1021/jacs.5b00929
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Magnetic Resonance Imaging Contrast by Improved Light-Driven Coordination-Induced Spin State Switch

Abstract: We present a fully reversible and highly efficient on-off photoswitching of magnetic resonance imaging (MRI) contrast with green (500 nm) and violet-blue (435 nm) light. The contrast change is based on intramolecular light-driven coordination-induced spin state switch (LD-CISSS), performed with azopyridine-substituted Ni-porphyrins. The relaxation time of the solvent protons in 3 mM solutions of the azoporphyrins in DMSO was switched between 3.5 and 1.7 s. The relaxivity of the contrast agent changes by a fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 46 publications
(16 reference statements)
1
142
0
Order By: Relevance
“…This work demonstrates the interest of using switchable ligands to achieve hysteresis without the need of cooperative effects, such as magnetic coupling or lattice interactions. This approach was successfully applied to obtain a photoswitchable Magnetic Resonance Imaging (MRI) contrast agent [55]. The relaxation time of the solvent protons was switched between 3.5 and 1.7 s improving the relaxivity of the contrast agent by a factor of 6.7.…”
Section: Spin State Change By Coordination Number Modulationmentioning
confidence: 99%
“…This work demonstrates the interest of using switchable ligands to achieve hysteresis without the need of cooperative effects, such as magnetic coupling or lattice interactions. This approach was successfully applied to obtain a photoswitchable Magnetic Resonance Imaging (MRI) contrast agent [55]. The relaxation time of the solvent protons was switched between 3.5 and 1.7 s improving the relaxivity of the contrast agent by a factor of 6.7.…”
Section: Spin State Change By Coordination Number Modulationmentioning
confidence: 99%
“…[6][7][8][9][10] However, spin switching of single molecules in solution or on surfaces at ambient temperatures is still challenging and only a few examples are known in the literature. spintronics, data storage, 3,4 switchable diamagnetic levitation 5 or responsive ("smart") contrast agents for magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] However, spin switching of single molecules in solution or on surfaces at ambient temperatures is still challenging and only a few examples are known in the literature. 10,[25][26][27] In both concepts the photoresponsive axial ligands are designed in such a way that only one photo isomer is capable of coordinating to the Ni 2+ . [15][16][17][18][19][20][21] We have demonstrated highly efficient and fatigue resistant light-driven coordinationinduced spin state switching (LD-CISSS) by adding photodissociable ligands [22][23][24] to a solution of a Ni 2+ -porphyrin (PDL approach) as well as by tethering azopyridines directly to the porphyrin ("record player" approach).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of azopyridines 7 and azoimidazoles 8 were reported to behave as photodissociable ligands, leading to changes in spin state upon photoisomerisation of metal porphyrins bearing these ligands. 9 Fuchter et al recently reported arylazopyrrole and arylazopyrazole photoswitches, which in some cases show long thermal half-lives and quantitative Z → E photoswitching. 10 Related arylazopyrazoles were used by Ravoo et al in switchable supramolecular host–guest systems.…”
mentioning
confidence: 99%